Advancing biological hazards risk assessment. (8th July 2019) - Messens, Winy; Hugas, Marta; Afonso, Ana; Aguilera, Jaime; Berendonk, Thomas U; Carattoli, Alessandra; Dhollander, Sofie; Gerner‐Smidt, Peter; Kriz, Nikolaus; Liebana, Ernesto; Medlock, Jolyon; Robinson, Tobin; et al.
Abstract: This paper focusses on biological hazards at the global level and considers the challenges to risk assessment (RA) from a One Health perspective. Two topics – vector‐borne diseases (VBD) and antimicrobial resistance (AMR) – are used to illustrate the challenges ahead and to explore the opportunities that new methodologies such as next‐generation sequencing can offer. Globalisation brings complexity and introduces drivers for infectious diseases. Cooperation and the application of an integrated RA approach – one that takes into consideration food farming and production systems including social and environmental factors – are recommended. Also needed are methodologies to identify emerging risks at a global level and propose prevention strategies. AMR is one of the biggest threats to human health in the infectious disease environment. Whereas new genomic typing techniques such as whole genome sequencing (WGS) provide further insights into the mechanisms of spread of resistance, the role of the environment is not fully elucidated, nor is the role of plants as potential vehicles for spread of resistance. Historical trends and recent experience indicate that (re)‐emergence and/or further spread of VBD within the EU is a matter of when rather than if. Standardised and validated vector monitoring programs are required to be implemented at an international level for continuous surveillance and assessment of potential threats. There are benefits to using WGS – such as a quicker and better response to outbreaks and additional evidence for source attribution. However, significant challenges need to be addressed, including method standardisation and validation to fully realise these benefits; barriers to data sharing; and establishing epidemiological capacity for cluster triage and response.